2015
DOI: 10.1182/blood.v126.23.1099.1099
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course and Management of Surgical Emergency in a Severe Hemophilia a Patient Under Weekly Subcutaneous Administration of a Bispecific Antibody to Factors IXa and X (ACE910)

Abstract: Background FVIIIa acts as a cofactor in the intrinsic pathway in which FIXa activates FX. ACE910 is a FIXa/FX-recognizing bispecific antibody that was designed to be a replacement for FVIIIa. Because of its nature, ACE910 is not affected by FVIII inhibitor. A clinical trial is now being conducted for the potential effect in the prophylactic treatment for bleeding hemophilia A patients. Here we present the perioperative care of a patient who had incidentally suffered from appendicitis and underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the primary study, ABR was calculated to be negligible with a baseline level of 13 IU dL −1 . Furthermore, in the phase 1/2 study, one non‐inhibitor patient in the 1 mg kg −1 week −1 group received emergency surgery for acute appendicitis without additional FVIII replacement therapy . This case suggested that surgical intervention might be possible in patients receiving emicizumab prophylaxis.…”
Section: Novel Treatment Strategies For Inhibitor Patientsmentioning
confidence: 99%
“…In the primary study, ABR was calculated to be negligible with a baseline level of 13 IU dL −1 . Furthermore, in the phase 1/2 study, one non‐inhibitor patient in the 1 mg kg −1 week −1 group received emergency surgery for acute appendicitis without additional FVIII replacement therapy . This case suggested that surgical intervention might be possible in patients receiving emicizumab prophylaxis.…”
Section: Novel Treatment Strategies For Inhibitor Patientsmentioning
confidence: 99%
“…10 Limited reports of surgery in patients on emicizumab alone or in conjunction with additional clotting factor have been reported, and an observational surgery study is ongoing. [11][12][13] During the trial, there were 5 thrombotic severe adverse events, including 2 thromboses and 3 thrombotic microangiopathy events. All of the events were in the setting of a breakthrough bleed treated with activated prothrombin complex (aPCC) at doses .100 IU/kg per day for more than 24 hours (5/8 treated with such intense regimen), whereas many breakthrough bleeds were treated with activated FVIIa (0/140 treated with activated FVIIa) alone or ,100 IU/kg per day or ,24 hours treatment with an aPCC and did not develop thrombotic events (0/70 treated with these less intense regimens).…”
Section: Emerging Bypassing Agentsmentioning
confidence: 99%